Peran Profitabilitas Dalam Memoderasi Pengaruh Rasio Likuiditas, Leverage, Dan Sales Growth Dalam Memprediksi Financial Distress Pada Perusahaan Sub Sektor Property Dan Real Estate - Linda Masni Hayati; Mu’minatus Sholichah (Universitas Muhammadiyah Gresik, 2022)
The purpose of this study is to analyze and describe the ability of profitability in moderating the effect of liquidity, leverage, and sales growth in predicting financial distress. The population in this study are property and real estate companies listed on the Indonesia Stock Exchange for the period 2017-2020, the sample of this study was taken using a purposive sampling method with a research sample of 156 financial statements from 39 companies. This research method uses quantitative methods. Data analysis was processed using Partial Least Squares (PLS) analysis with the help of Smart-Pls 3.0 software. The results of this study indicate that the ratio of liquidity and profitability has a negative and significant effect on financial distress. Meanwhile, leverage and sales growth have no effect on financial distress. Profitability can moderate the relationship between liquidity and financial distress. Meanwhile, profitability cannot moderate the relationship between Leverage and Sales growth on financial distress.